Optimalisasi Wakaf dalam Mengembangkan Pariwisata Halal di Kampung Al-Munawar - M Fachry Zaiman; Nilawati Nilawati; Nurfala Safitri (Wakil Rektor III Bidang Kemahasiswaan dan Kerjasama, 2020)
The huge tourism potential has become the government's attention in an effort to revive the Indonesian economy such as Halal Tourism. Waqf as empowerment of property in Islam has the potential to develop the economy of the community through Halal Tourism. Halal Tourism Kampung Al-Munawar Palembang is one example of halal tourism objects that come from waqf activities around the community. This study aims to determine the strategy of Waqf Optimization in Developing Halal Tourism in Al-Munawar Village in Palembang. The results of the study indicate the need for strategies such as raising public awareness to represent, increasing the quality of professional and competent Nazhir resources, making waqf as a supporter of Halal Tourism, and making MSME practitioners who have received assistance from wakaf funds (mauquf 'alaih) as providers of waqaf (waqif)